(untitled) (Docentes 2.0 Journal, 2021)
The confinement situation due to COVID 19 has led to important transformations at the educational level, showing a substantial increase in educational difficulties, especially in students with low income due to the lack of connectivity and access to technological equipment. The essay presented below seeks to describe some aspects related to socio-educational inequalities in the Colombian context, a product of confinement due to coronavirus, generating reflections typical of teaching work and favoring pedagogical transformation based on analysis. The total or partial closure of educational institutions affected a considerable number of students, increasing levels of inequality, access to education and school dropouts, being evident the little preparation of the educational system for the contingency. To address these adverse situations, from the teaching perspective it is necessary to retake the educational processes from curricular and evaluative flexibility, considering the new pedagogical reality that both Educational Institutions and teachers must assume. Schools must replace their processes, from the redesign of strategies and methodologies coinciding with the historical needs presented in this time of adversity.